Using long-term experimental restoration of agroecosystems in Aotearoa New Zealand to improve implementation of Nature-based Solutions for climate change mitigation - Buckley, Hannah L.; Hall, David; Jarvis, Rebecca M.; Smith, Valance; Walker, Leilani A.; Silby, Jeff; Hinchliffe, Graham; Stanley, Margaret C.; Sweeney, Aileen P.; Case, Bradley S. (Frontiers in Forests and Global Change, 2023)
Tree planting has long played a major role in the New Zealand Government’s approach to climate mitigation and is increasingly understood as important for climate adaptation. However, large-scale tree planting in Aotearoa New Zealand has been dominated by exotic species. Although there is growing public and expert support for using native species for forest revegetation in farm landscapes, there are two key barriers. Firstly, the lack of ecological and economic data on native species performance in different environmental conditions. Secondly, policy and market-related mechanisms associated with carbon sequestration, such as the New Zealand Emissions Trading Scheme, favour the continuing use of exotic tree species, especially Pinus radiata, over native species. Consequently, there are strong incentives for exotic forests and insufficient financial support for natives, even when native forest re-establishment is often the preference of landowners, Indigenous peoples, and local communities. The AUT Living Laboratories Programme is a long-term, transdisciplinary, experimental restoration research programme aimed at addressing scientific, social, and economic knowledge gaps for native revegetation as a Nature-based Solution on farmland soils. Here, we present the project design and establishment information from the three experimental restoration sites, which vary in native species composition, planting configuration, and environmental and socio-cultural context. Each site involves partnerships with Indigenous communities, specifically Ngāti Whātua Ōrākei, Ngāti Manuhiri and Ngāti Pāoa, to value and embed mātauranga Māori as Indigenous knowledge. Monitoring carbon sequestration along with changes in ecological functions and outcomes, including native biodiversity, will be critical to ensure that large-scale tree-planting aligns with the government’s strategies for climate change, native biodiversity and economic prosperity.